2011
DOI: 10.1038/ki.2010.484
|View full text |Cite
|
Sign up to set email alerts
|

Progressive podocyte injury and globotriaosylceramide (GL-3) accumulation in young patients with Fabry disease

Abstract: Progressive renal failure often complicates Fabry’s disease. However, the pathogenesis of Fabry nephropathy is not well understood. We applied unbiased stereological methods to the study of the electron microscopic changes of Fabry nephropathy and the relationship between glomerular structural parameters and renal function in young Fabry patients. Renal biopsies from 14 (M/F=8/6) enzyme replacement therapy (ERT)-naive Fabry patients (median age 12 years; range 4–19 years) and 9 (M/F=6/3) normal living kidney d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
170
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(191 citation statements)
references
References 33 publications
8
170
1
12
Order By: Relevance
“…The marked deficiency or absence of GAL activity results in the systemic accumulation of globotriaosylceramide and related glycosphingolipids within the lysosomes, particularly in microvascular endothelial cells, vascular smooth muscle cells, renal tubular cells, podocytes, and cardiomyocytes 3, 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…The marked deficiency or absence of GAL activity results in the systemic accumulation of globotriaosylceramide and related glycosphingolipids within the lysosomes, particularly in microvascular endothelial cells, vascular smooth muscle cells, renal tubular cells, podocytes, and cardiomyocytes 3, 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Atlikus inkstų biopsiją, galimas platus histopatologinių pakitimų spektras. Šviesinės mikroskopijos metu randama podocitų ir epitelinių ląstelių vakuolizacija kartu su mezangiumo išsiplėtimu yra būdin-gas Fabry ligos bruožas, vėliau gali progresuoti iki segmentinės ir globalinės glomerulosklerozės [23]. Elektroninės mikroskopijos metu nustatomi tipiški Fabry ligos pakitimai -"zebra" kūneliai (2 pav.).…”
Section: Literatūros Apžvalgaunclassified
“…Tai -glikosfingolipidų sankaupos podocituose, glomerulų endotelinėse, mezangiumo ir intersticinėse ląstelėse. Pakitimai podocituose progresuoja su amžiumi ir tiesiogiai koreliuoja su proteinurijos dyžiu [23]. Negydomas progresuojantis inkstų pažeidimas yra dažniau-sia Fabry liga sergančių vyrų mirties priežastis.…”
Section: Literatūros Apžvalgaunclassified
See 1 more Smart Citation
“…30 Renal symptoms. Najafian et al 51 reported storage of GL3 in biopsied kidneys as early as age 4 years, with GL3 inclusions in all glomerular cell types. Reports of clinical renal involvement in the pediatric population with Fabry disease are limited but may include microalbuminuria, proteinuria, and reduced glomerular filtration rates.…”
Section: Fabry Disease During Early Childhoodmentioning
confidence: 99%